Accidental guide catheter fracture in mechanical thrombectomy. Issue 3 (June 2019) - Al-Schameri, Abdul Rahman; Deshmukh, Aviraj; Debaseh, Hadi; Griessenauer, Christoph; Killer-Oberpfalzer, Monika
Endovascular thrombectomy is now the standard of care for large vessel occlusion stroke. The aim is to achieve rapid and complete recanalisation while avoiding complications. Apart from the conventional complications of neurointerventional procedures, mechanical thrombectomy has its unique set of complications, inherent to the disease pathophysiology. We describe an unusual complication of catheter fracture and subsequent distal embolisation into the cerebral vasculature, which was noticed 24 hours after the procedure. Due to a lack of clinical consequences, we decided to manage it conservatively. The patient died within the following few days from respiratory complications unrelated to the stroke or the endovascular thrombectomy procedure. Consequently, we were able to retrieve the fractured segment and carry out histopathological analysis, which helped us to identify exactly its origin from the guide catheter. We believe that systematic reporting and database compilation of such device-related complications will aid in the design and development of neurointerventional devices in the future.